Microradiosurgical cortical transections generated by synchrotron radiation. Issue 6 (September 2015) - Romanelli, Pantaleo; Fardone, Erminia; Bucci, Domenico; Battaglia, Giuseppe; Bräuer-Krisch, Elke; Requardt, Herwig; Le Duc, Geraldine; Bravin, Alberto
Abstract Purpose Microplanar X-ray beams (microbeams) originated by synchrotron sources have been delivered to the visual brain cortex regions in rodents to create microscopically narrow lesions. The effects of microbeams mimic those generated by microsurgical subpial transections (also known as multiple subpial transections) but are obtained in a low-invasive way. Methods Image-guided atlas-based microbeam cortical transections have been generated on seven 1 month-old Wistar rats. An array of 10 parallel beams of 25 microns in thickness and spaced of 200 micron center-to-center was centered on the visual cortex and deposited an incident dose of 600 Gy. Results The procedure was well tolerated by rats. After recovery, rats showed regular behavior, no sign of gross visual impairment and regular weight gain. After 3 months, rats were sacrificed and brains histologically examined. Cortical transections resembling those obtained through a surgical incision were found over the irradiated region. Remarkable sparing of the cortical columns adjacent to the transections was observed. No sign of radionecrosis was evident at least at this time point. Conclusions The visual brain cortex transected by synchrotron-generated microbeams showed an incision-like path of neuronal loss while adjacent non irradiated columns remained intact. These preliminary findings, to be further investigated also using other techniques, suggest that microbeam radiosurgery can affect the cortex at a cellular level providing a potential novel and attractive tool to study cortical function.